Reconstruction of late Holocene paleoenvironment in Kongsfjorden, West Spitsbergen. Based on analysis of benthic foraminifera - Danielsen, Kim-André (UiT Norges arktiske universitet, 2017)
The benthic foraminiferal fauna of two marine sediment records from the Kongsfjorden Trough and the inner part of Kongsfjorden were analyzed to reconstruct the paleoenvironmental development throughout the last ~ 2000 years. A generally cold period is evident in both records, lasting from ~ 700 to 1400 CE at the Kongsfjorden Trough and from ~ 350 to 1200 CE in the inner part of Kongsfjorden, with low to moderate influence of Atlantic Water at both sites. However, the record from the inner part of Kongsfjorden show more fluctuating conditions, possibly due to high influence of local water masses. In both records, the cold period is followed by a period of ameliorated conditions, characterized by an abrupt increase of the benthic foraminiferal flux from ~ 1400 to 1650 CE at the Kongsfjorden Trough, and a gradual increase in the relative abundance of N. labradorica from ~ 1200 to 1550 CE in the inner part of Kongsfjorden. This indicates increased influence of Atlantic Water at both sites, and is correlated to correspond to the Medieval Warm Period. The record from the Kongsfjorden Trough stops at ~ 1650 CE as the core top is missing. In the inner part of Kongsfjorden a period of rapidly deteriorated conditions follows from ~ 1550 to 1650 CE, characterized by an abrupt increase of % E. excavatum f. clavata and a corresponding decrease of % N. labradorica. From ~ 1650 to 1900 CE the trend changes with gradually improved conditions. The period from ~ 1550 to 1900 CE is correlated to correspond to the Little Ice Age. The last ~ 100 years of the NP14-Kb3 record is characterized by an accelerated increase of % N. labradorica, reaching maxima in relative abundance. This possibly indicates the highest influence of Atlantic Water throughout the record, and is correlated to correspond to the Modern Warming.